Alkaline protease from bacillus pumilus: a study on their biodegradative, dehairing and destaining activity - KATHIRVEL PREETHI; GOLDY PRIMO BERYL (International Journal of Pharma and Bio Sciences, 2017)
Proteolytic Bacillus sp. isolated from tannery effluent, were screened for their ability to produce alkaline protease on saline skim milk agar plates (pH-9). Bacillus pumilus exhibited vibrant clear zone of 30mm diameter. Highest alkaline protease activity (466 Units/ml) was recorded on 72 hours of incubation. Activity was higher at 37°C, pH-9, in lactose and beef extract. Biode gradation of chicken feather using Bacillus pumilus showed 56% of feather degradation. The fermented silage was air-dried at 50°C for 12 hours. Proximate composition of the hydrolyzed feather powder was found to be 5.8% crude protein, 11% fat, 3.6% carbohydrate, 2.4% ash, and 1.2% crude fiber, which indicated its use in livestock feeds and/or as a biofertilizer. Alkaline protease from Bacillus pumilus also showed excellent dehairing activity, when dip and spray method was employed. Moderate dehairing activity was observed in paint method. The enzyme acted as an efficient detergent additive and complete destaining of stained clothes was observed within 15 minutes of incubation. Protein content of partially purified enzyme was 28 mg/ml and SDS-PAGE results revealed its molecular weight to be 28 kDa.